The Effect of Population and HDI on Poverty Levels in Pakpak Bharat District - Hardianti Manik; Henni Tumangger; Wanda Pratama (International Journal of Business and Applied Economics, 2023)
The number of poor people in pakpak bharat from 2010 to 2020 has increased from year to year; in 2010, the number of poor people was 176,830.00, and in 2020, it rose to 311,584.00. The aim of this research is to determine the effect of population and the human development index (IPM) partially and simultaneously on the level of poverty in Pakpak Bharat district. The location of this study in Pakpak Bharat district used time series data from 2010 to 2010 with two independent variables and one dependent variable. The type of data used in this study was secondary data obtained from the central statistics agency (BPS) in Pakpak Bharat district, which was then processed and analyzed using multiple linear regression analysis. The results of the analysis were obtained: (1) population has a significant effect on the poverty rate in Pakpak Bharat district; (2) HDI has a significant effect on the poverty rate in Pakpak Bharat district; and (3) simultaneously, population and HDI have a significant effect on the poverty rate in Pakpak Bharat district.